Institusi Ekonomi dan Penyaluran Kredit: Pengaruh Suku Bunga, Pajak, dan Investasi di ASEAN-5 - Prestianawati, Silvi Asna; Aprilia, Yuyun Fahira; Rasli, Amran; Chanu, Ibemcha; Fawwaz, Muhammad (SAFE-Network, 2025)
This research analyzes the role of economic institutions—reflected through interest rates, tax policies, and investment climate—in influencing domestic credit distribution in ASEAN-5 countries. Employing a descriptive quantitative approach, the study uses secondary data from the World Bank covering the period 2013–2022, focusing on Indonesia, Singapore, Malaysia, the Philippines, and Thailand. Panel data regression is used to estimate the effects of institutional variables. The findings reveal that interest rates and the number of new business registrations—an indicator of investment climate—positively and significantly impact domestic credit distribution. Conversely, tax levels show a significant negative effect, indicating that lower tax burdens are associated with greater credit distribution. These results underscore the importance of institutional quality in shaping financial intermediation within ASEAN-5 economies and provide insights for policymaking to strengthen credit markets.